The Financial Performance Analysis of The Life and The General Insurance, and The Reinsurance in Indonesia through The Non-Solvency Ratio Approach - Nurdiana Agustina; Ika Sisbintari; Hari Karyadi (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2025)
The financial performance analysis is an assessment process by reviewing, calculating, measuring, interpreting, and then providing solutions to a company’s financial statements for at least two periods. This research uses the financial statement analysis theory. The purpose of this study is to analyze the financial performance of the insurance industry in Indonesia for the period 2020-2024. The analysis uses a quantitative-descriptive method with a financial ratio analysis approach in the form of the investment adequacy ratio, the liquidity ratio, and the ratio of cost to premium income. The focus of this study is the life insurance, the general insurance, and the reinsurance industries, which are analyzed both internally and externally of then regulatory industry standards. The analysis results conducted on the investment adequacy ratio indicate that the insurance industry complies with the minimum 100 percent value set by regulations. In the internal liquidity ratio, the company’s performance is still less liquid, but by industry standards, it is considered good because the current assets are greater than the current liabilities. Then, in the ratio of cost to premium income, the company’s management is inefficient, especially in the commission cost account, which requires a fair calculation considering that it is borne by policyholders in the form of premium payments. But, the insurance industry in this study is still a recommendation and choice for the nominee of policyholder who will join according to their needs.